Mechanics precision grinding brittle materials - Ngoi, Bryan Kok Ann. (2008)
This project aims at gaining a better understanding of the mechanics of precision grinding of brittle materials. Indentation and scribing experiments on brittle materials were carried out to study crack initiation and propagation, brittle-ductile transition and material removal mechanism. The results of indentation and scribing tests show that brittle materials can be machined in a ductile manner when penetration depth is less than a critical value. Single point diamond turning of brittle materials, both as an alternative machining technique in its own right and as a model for certain parameters involved in grinding, was performed. Experimental results show that the properties of the workpiece material have a considerable influence on the critical depth of cut. Mirror surfaces are more prone to be generated on single crystal silicon than glasses. A smooth surface with a roughness in nano-scale was produced on silicon by properly controlling machining parameters. Tool wear mechanism in diamond cutting of glasses was investigated.